Indian design code for slender reinforced concrete columns - Lau, Lewis Kah Cheong. (2013)
This report evaluates the Indian design code IS 456:2000 for slender reinforced concrete columns, by analyzing the failure loads of pinned-ended columns under short term loading and uniaxial bending. The report also aims to study the influences of parameters such as slenderness ratio, eccentricity ratio, concrete strength, reinforcement strength and steel ratio.